Effects of mining chemicals on fish: exposure to tailings containing Lilaflot D817M induces CYP1A transcription in Atlantic salmon smolt. (December 2015) - Olsvik, Pål; Urke, Henning; Nilsen, Tom; Ulvund, John; Kristensen, Torstein
Abstract Background Mine tailings, containing metals and production chemicals such as flotation chemicals and flocculants, may pose an environmental threat to aquatic organisms living in downstream ecosystems. The aim of this work was to study to which degree Lilaflot D817M, a flotation chemical extensively used by the mining industry, represents a hazard for migrating salmon in rivers affected by mining activity. Smoltifying Atlantic salmon were exposed to four concentrations of iron-ore mine tailings containing residual Lilaflot D817M [water versus tailing volumes of 0.002 (Low), 0.004 (Medium), 0.013 (High) and 0.04 (Max)]. After 96 h of exposure, gill and liver tissues were harvested for transcriptional responses. Target genes included markers for oxidative stress, detoxification, apoptosis and DNA repair, cell signaling and growth. Results Of the 16 evaluated markers, significant transcriptional responses of exposure to tailings enriched with Lilaflot D817M were observed for CYP1A, HSP70 and HMOX1 in liver tissue and CYP1A in gill tissue. The significant induction of CYP1A in both liver and gills suggest that the flotation chemical is taken up by the fish and activates cytochrome P450 detoxification via phase I biotransformation in the cells. Conclusions The overall weak transcriptional responses to short-term exposure to Lilaflot D817M-containing iron-ore tailings suggest that the mining chemical has relatively low toxic effect on fish. The underlying mechanisms behind the observed CYP1A induction should be studied further.